Cinema of Thought: A Dialectic of Body and Brain in Turkish Art Cinema - Serdar Öztürk; Waseem Ahad (Philosophies, 2025)
Can films contribute to the production of thought? Or, to put the question more radically, can films generate thought on their own, or can there be films that think the unthought? When thought is equated with rationality, logic, concepts, generalizations, and abstractions, the answer can be “no” at the outset, particularly when ordinary people in the flow of their daily lives typically turn to mass films for escapism. On the other side of the spectrum, among the philosophers and social scientists who argue that cinema might contain serious intellectual elements, there is no general approach that radically challenges the meaning that ordinary people may attach to films. By focusing on Deleuze’s concepts of “body-cinema” and “brain-cinema”, this article aims to showcase how films can philosophize on their own. While going beyond the traditional association of thought with mind and reasoning, this article explores the diffused location of thought, existing in our very sensations and emotions. This article analyzes some of the significant films from the Turkish art cinema—both old and recent—to explore how thought is constituted with reference to the human body and brain in cinema.